An assessment of the relative abundance of normal and parasitized white leafhopper Cofana spectra (Homoptera: Cicadellidae) affecting the paddy plants in West Bengal, India. (March 2014) - Mitra, Sangita; Harsha, Rupa; Hazra, Niladri; Mazumdar, Abhijit
<x content-type="archive" xml:space="preserve">Abstract</x> The homopteran bug Cofanaspectra (Distant), also known as the white leafhopper, is abundant in rice-growing areas of India (West Bengal, Northeast and southern states) and considered as a minor pest of paddy. The proportion of Cofanaspectra and the endoparasitoid Halictophagus australensis Perkins varied between months and demonstrated peak abundance during March to May and October to December, which corresponded with the rice cropping periods boro (winter crop) and aman (monsoon crop), respectively. There was a negative correlation between the influence of environmental factors (air temperature, rainfall and relative humidity) and the abundance of normal and parasitized C. spectra. The proportion of parasitization by H. australensis varied with the relative abundance of C. spectra. The effect of stylopization on C.spectra by the Strepsiptera may be one of the factors attributable to the suppression of the population levels of the paddy pest.